PENGARUH MEDIA POP UP BOOK TERHADAP HASIL BELAJAR IPAS KELAS IV SD INPRES 24 KABUPATEN - Chindy Aprilia; Desti Rahayu; Gika Apia (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The aim of this rsearch. The purpose of this study is to determine the influence of pop up book media on the learning outcomes of science and science, plant parts and their functions in grade IV of SD Inpres 24 Regency. This study is a pre-experimental research with a one-group pretest-postest research design. The sample used was all grade IV students totaling 19 student. The data collection technique used is a test (pretest-posttest). The data analysis technique consists of 3 stages, namely the descriptive stage, normality test, and hypothesis test. The results of the prettest instrument item reality test were obtained 0.902 and the posttest was obtained 0.981. From the data analysis, descriptive pretest data with a mean value of 54.68 while posttest with a mean value of 74.37.From data analysis, the normality test of asymp.sig was obtained, the pretest data was 0.068 > 0.05, while the posttest was 0.073 > 0.05 from this data showed that it was normally distributed. The results of the T-test were obtained. 001 where the significant value obtained was < 0.05 which means that Ha in this study was accepted and Ho was rejected. Thus, it can be concluded that there is an influence of pop up book media on the learning outcomes of science and science materials Plant Parts and their functions in grade IV students of SD Inpres 24 Sorong Regency.